Concentrações de ácido indolbutírico e tipos de substrato na propagação vegetativa de lichia - Smarsi, Ronny Clayton (2008)
The objective of the present research was to evaluate the effect of the IBA application and different kinds of substrates in the vegetative propagation of litchi by air layering technique. The air layering had been done in semi-hardwood, healthy and vigorous branches of cultivar Bengal, in stock plants of 12 years old. The branches had been ring-girdled, 1,5 cm of width, and the exposed wound treated with different IBA concentrations (0, 1000, 2000, 3000 and 4000 mg.L-1), enclosed with three moistened substrates (plantmax®, humus and sphagnum moss), involved with transparent plastic and tied in the two extremities. After 84 days, it was evaluated the length of root (cm), number of root expressed in notes from 0 to 5, percentage of callus and rooting. The best results in the vegetative propagation of litchi, cultivar Bengal, by air layering technique were obtained using plantmax® and IBA between 2.166 and 2.430 mg.L-1. The use of humus combined with concentrations between 2.175 and 2.250 mg.L-1 of IBA, also gave good results in the development of air layering. The poor success independently of IBA concentration was gotten with the use of sphagnum moss.